Insect hemolymph coagulation: Kinetics of classically and non-classically secreted clotting factors. - Schmid, M.R.; Dziedziech, A.; Arefin, B.; Kienzle, T.; Wang, Z.; Akhter, M.; Berka, J.; Theopold, U. (Insect Biochemistry and Molecular Biology, 2019)
In most insects, hemolymph coagulation, which is analogous to mammalian blood clotting, involves close collaboration between humoral and cellular components. To gain insights into the secretion of cellular clotting factors, we created tagged versions of three different clotting factors. Our focus was on factors which are released in a non-classical manner and to characterize them in comparison to a protein that is classically released, namely Glutactin (Glt). Transglutaminase-A (Tg) and Prophenoloxidase 2 (PPO2), both of which lack signal peptide sequences, have been previously demonstrated to be released from plasmatocytes and crystal cells (CCs) respectively, the two hemocyte classes in naïve larvae. We found that at the molecular level, Tg secretion resembles the release of tissue transglutaminase in mammals. Specifically, Drosophila Tg is associated with vesicular membranes and remains membrane-bound after release, in contrast to Glt, which we found localizes to a different class of vesicles and is integrated into clot fibers. PPO2 on the other hand, is set free from CCs through cytolysis. We confirm that PPO2 is a central component of the cytosolic crystals and find that the distribution of PPO2 appears to vary across crystals and cells. We propose a tentative scheme for the secretory events during early and late hemolymph coagulation.